Corn yield, spacing and intercropping modalities with Brachiaria brizantha in no-tillage system - Borghi, Emerson; Crusciol, Carlos Alexandre Costa (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this research was to evaluate the effects on corn yield of different modes of corn intercropping with Brachiaria brizantha cv. Marandu. The experiment was carried out in field conditions, in 2002/2003 and 2003/2004, at Fazenda Experimental Lageado (Unesp), in Botucatu, SP, Brazil. The experimental design was the randomized complete block, as a factorial 2x4, with four replications. The treatments were two row spacings of corn (0.45 and 0.90 m) and four intercropping modalities: single corn; corn intercropped with B. brizantha in the row of sowing; corn intercropped with B. brizantha in space between two rows; and corn intercropped simultaneously with B. brizantha in the row and in the inter-row. The consortium modalities and the spacing used did not damage nitrogen absorption, neither for the corn nor the forage. Corn grains productivity in 0.45 m row spacing was lower with the row and inter-row Brachiaria consortium. Depending on agricultural year, grain yield is greater in the reduced row spacing, when intercropping with Brachiaria, independently of the modality.
Keywords: Zea mays; tillage systems; crop-livestock integration; consortium